EFEKTIVITAS GAYA KEPEMIMPINAN PIMPINAN TERHADAP TINGKAT KESIAPAN KARYAWAN DALAM BEKERJA - Sari, Ratna Deli (JURNAL PERSPEKTIF BISNIS, 2013)
A leader must be able to precisely direct individual goals to organizational goals. Leadership Style is one aspect of leadership in optimizing the ability of natural resources, financial and human resources to achieve organizational goals. The most appropriate leadership style will depend on the function of the leader, subordinates and the situation. Leadership effectiveness can be achieved if the leadership style can adjust to the level of development of the subordinate to the existing situation.In this study, the tool used is a situational leadership style that conveyed by Hersey and Blanchard. Situational leadership model, it can measure the extent of the effectiveness of leadership styles used by the leadership. The method used is descriptive survey. Data obtained, using questionnaires, interviews, and other internal data that is needed.The results of these studies indicate that leadership style and development level of subordinates are not on the same level, still has not been effective results. Thus, it can be concluded that the effectiveness of leadership style that is used is still low, amounting to 57%. With these results it is, the level of employee satisfaction is low there is a leadership shown by the percentage by 56%.Â Keyword: leader, subordinates, situational leadership, Leadership effectiveness